A Systematic Review of DNA Methylation and Preterm Birth in African American Women - Barcelona de Mendoza, Veronica (Biol Res Nurs, 2016)
BACKGROUND: The causes of many cases of preterm birth (PTB) remain enigmatic. Increased understanding of how epigenetic factors are associated with health outcomes has resulted in studies examining DNA methylation (DNAm) as a contributing factor to PTB. However, few studies on PTB and DNAm have included African American women, the group with the highest rate of PTB. METHODS: The objective of this review was to systematically analyze the existing studies on DNAm and PTB among African American women. RESULTS: Studies (N = 10) were limited by small sample size, cross-sectional study designs, inconsistent methodologies for epigenomic analysis, and evaluation of different tissue types across studies. African Americans comprised less than half of the sample in 50% of the studies reviewed. Despite these limitations, there is evidence for an association between DNAm patterns and PTB. CONCLUSIONS: Future research on DNAm patterns and PTB should use longitudinal study designs, repeated DNAm testing, and a clinically relevant definition of PTB and should include large samples of high-risk African American women to better understand the mechanisms for PTB in this population.